A Combination of Freeze Drying and Microwave Vacuum Drying of Duck Egg White Protein Powders - Zhou, B.; Zhang, M.; Fang, Zhongxiang; Liu, Y. (Taylor & Francis, 2014)
High energy consumption during freeze drying (FD) is a major concern that limits its application on common food product manufacturing. In this research, fresh duck egg white protein (FDEWP) powder and desalted duck egg white protein (DDEWP) powder were obtained by a combined two-stage tandem drying technologies (FD and microwave–vacuum drying [MVD]) in order to reduce energy consumption while maintaining good product quality. The results showed that the drying time for the FDEWP and DDEWP powders was significantly decreased by FDþMVD compared to those obtained by the FD-only process. The FDEWP powders dried by FDþMVD had a better color (higher L and lower b), lower apparent density, and lower foaming stability but higher emulsifying index than those dried by FD only. The DDEWP powder dried by FDþMVD had a product quality similar to that of FDEWP powder, suggesting that the DDEWP powder could be widely used as a food ingredient.